Adeno‐associated virus serotype 1‐based gene therapy for FTD caused by GRN mutations. Issue 10 (16th September 2020) - Hinderer, Christian; Miller, Rod; Dyer, Cecilia; Johansson, Julia; Bell, Peter; Buza, Elizabeth; Wilson, James M.
Abstract: Objective: Dominant loss‐of‐function mutations in the gene encoding the lysosomal protein, progranulin, cause 5‐10% of frontotemporal dementia cases. As progranulin undergoes secretion and endocytosis, a small number of progranulin‐expressing cells can potentially supply the protein to the entire central nervous system. Thus, gene therapy is a promising treatment approach. Methods: We evaluated adeno‐associated viral vector administration into the cerebrospinal fluid as a minimally invasive approach to deliver the granulin gene to the central nervous system in a murine disease model and nonhuman primates. Results: In progranulin‐deficient mice, vector delivery into the lateral cerebral ventricles increased progranulin levels in the cerebrospinal fluid and normalized histological and biochemical markers of progranulin deficiency. A single vector injection into the cisterna magna of nonhuman primates achieved CSF progranulin concentrations up to 40‐fold higher than those of normal human subjects and exceeded CSF progranulin levels of successfully treated mice. Animals treated with an adeno‐associated virus serotype 1 vector exhibited progranulin expression fivefold higher than those treated with an AAV5 vector or the AAV9 variant, AAVhu68, apparently due to remarkably efficient transduction of ependymal cells. Progranulin expression mediated by adeno‐associated viral vectors was well tolerated in nonhuman primates with no evidence of dose‐limiting toxicity, even at vector doses that induced supraphysiologic progranulin expression. Interpretation: These findings support the development of AAV1‐based gene therapy for frontotemporal dementia caused by progranulin deficiency.